3D Printing Hydrogel-Based Soft and Biohybrid Actuators: A Mini-Review on Fabrication Techniques, Applications, and Challenges - Sun, Wenhuan; Schaffer, Saul; Dai, Kevin; Yao, Lining; Feinberg, Adam; Webster-Wood, Victoria (Frontiers in Robotics and AI, 2021)
Stimuli-responsive hydrogels are candidate building blocks for soft robotic applications due to many of their unique properties, including tunable mechanical properties and biocompatibility. Over the past decade, there has been significant progress in developing soft and biohybrid actuators using naturally occurring and synthetic hydrogels to address the increasing demands for machines capable of interacting with fragile biological systems. Recent advancements in three-dimensional (3D) printing technology, either as a standalone manufacturing process or integrated with traditional fabrication techniques, have enabled the development of hydrogel-based actuators with on-demand geometry and actuation modalities. This mini-review surveys existing research efforts to inspire the development of novel fabrication techniques using hydrogel building blocks and identify potential future directions. In this article, existing 3D fabrication techniques for hydrogel actuators are first examined. Next, existing actuation mechanisms, including pneumatic, hydraulic, ionic, dehydration-rehydration, and cell-powered actuation, are reviewed with their benefits and limitations discussed. Subsequently, the applications of hydrogel-based actuators, including compliant handling of fragile items, micro-swimmers, wearable devices, and origami structures, are described. Finally, challenges in fabricating functional actuators using existing techniques are discussed.